RELATIONSHIP BETWEEN MATERNAL AGE AND PARITY WITH THE INCIDENCE OF POSTPARTUM HEMORRHAGE IN LABORING MOTHERS IN THE MATERNITY ROOM - Dwi Saputri MS; Ana Sapitri; Indah Permata (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Maternal Mortality Rate (MMR) or Maternal Mortality Ratio (MMR) results of the 2023 Indonesian Demographic and Health Survey (SDKI) have been published by the government MMR according to the 2023 SDKI is 359/1000.000 live births. The purpose of this study was to determine the relationship between maternal of mother age and parity with the incidence of postpartum hemorrhage events in motherhood in the maternity room of Prabumulih City Hospital in 2023. This research uses an Analytical Survey using a Cross Sectional approach. The study population was all women who gave birth in the General Hospital Prabumulih City in 2023, amounting to 2.242 people. The number of sampels in this study was 399 responden. In the univariate analysis, it was found that 144 respondents had a high risk age (33,6%) and 225 respondents (66,4%) had a low risk age. Mothers at high risk were 74 repondents (21,8%) and mothers at low risk were 265 respondents (78,2%). Bivariat analysis showed that maternal age had a significant relationship with postpartum hemorrhage (p-value 0,000), maternal parity had a significant relationship with postpartum hemorrhage (p-value 0,000). The conclusion from this research is that there is a significant relationship between maternal age and parity and the incidence of postpartum hemorrhage in mothers giving birth in the maternity ward at the Prabumulih City Regional General Hospital in 2023.